Flexicurity capitalism foundations, problems and perspectives - Flaschel, Peter, 1943-; Greiner, Alfred (New York ; Oxford : Oxford University Press, 2012)
This title provides serious discussion and feasible mathematical models to provide a basic framework for a 'flexicurity' economic system - labour market reform that combines flexibility in the hiring and firing processes of firms with security in the employment and income of the workforce.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Manpower policy; Labor policy; Job security; Capitalism -- Social aspects